Governing the Local: Sovereignty, Social Governance and Community Safety - Kevin Stenson (Social Work & Society, 2008)
There has been much commentary about the re-ordering of the relations between nation state government, geographical territory, and populations in the advanced liberal democracies. This is seen as a product of: increasing demographic and cultural diversity due to legal and illegal migration; economic, cultural, and political global interdependence; footloose mobility of capital and the outsourcing of jobs to poorer countries; the growing power of international corporations and financial markets; and the growth of supra-national bodies like the European Union and The North Atlantic Free Trade Association, the World Trade Organisation, and (debatably), the UN. These developments are held to be associated with the gradual demise of the model of the increasingly secular nation state first crystallised by the Treaty of Westphalia in 1648. This conception provided a mutual, guarantee of states' jurisdiction over territory and populations through their legitimated attempts to monopolise the use of force. Though, the relations between these states have always been asymmetrical and often challenged (Hunter 1998). This article explores the continuum of commentary about these issues, including tensions between a cosmopolitan universalistic ideology deployed by liberal professional elites and the more communitarian and nationalist ideologies deployed by politicians of the right. The latter emphasise the struggle for sovereign control of populations and neighbourhoods at local level. In exploring these themes this article develops a realist version of Governmentality theory, highlighting the interaction between governance from above and below. This is applied in a grounded way to the analysis of the local governance of community safety in the UK Thames Valley region. It identifies the political economic shifts in the region, then examines the local governmental responses to these changes, emphasising how, notwithstanding the hegemony of the political right in the region, well organised liberal networks of crime control professionals. They created a protective shield of cosmopolitan, universalistic values and policies against deeper communitarian and nationalistic sensibilities and strategies of governance. This facilitated the pioneering of a range of liberal, holistic, community safety initiatives that reconstruct `social` governance at local levels. Finally, the wider implications of these governmental shifts are explored, and tensions in the struggles to maintain collective solidarity in the contested terrain of the nation state, represented at local level.